2015
DOI: 10.15376/biores.11.1.759-771
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Sulfuretin and Butin from Rhus verniciflua Stokes Using Medium-pressure Liquid Chromatography and their Tyrosinase Inhibitory Effects

Abstract: The aim of this study was to separate antityrosinase compounds of the ethyl acetate fraction from Rhus verniciflua Stokes using medium pressure liquid chromatography. Among the different fractions, the Fr.6 fraction showed the highest antityrosinase capacity (96.5%), followed by the Fr.5 fraction (85.6%). The Fr.1 fraction showed the lowest antityrosinase capacity (12.4%). Bioactivity-guided fractionation of Fr.5.5 and Fr.6.4 led to the isolation and identification of butin and sulfuretin. Then the inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Furthermore, a carbonyl carbon at δ C 181.2 (C-4), together with an olefinic group [δ C 145.7 (C-3), and 111.9 (C-2)] observed in the 13 C NMR spectrum indicated that 5 was aurone skeleton (Figure 1) [13]. Based on the above evidence and comparison with reported data [22], compound 5 was identified as 7,3',4'-trihydroxyaurone, named sulfuretin. This compound was also isolated from the heartwood of D. odorifera [11].…”
Section: Resultssupporting
confidence: 66%
“…Furthermore, a carbonyl carbon at δ C 181.2 (C-4), together with an olefinic group [δ C 145.7 (C-3), and 111.9 (C-2)] observed in the 13 C NMR spectrum indicated that 5 was aurone skeleton (Figure 1) [13]. Based on the above evidence and comparison with reported data [22], compound 5 was identified as 7,3',4'-trihydroxyaurone, named sulfuretin. This compound was also isolated from the heartwood of D. odorifera [11].…”
Section: Resultssupporting
confidence: 66%